Epífitos vasculares sobre Pseudobombax aff. campestre (malvaceae) em complexos rupestres de granito no sul do Espírito Santo, Brasil - Couto, Dayvid Rodrigues (2013)
The epiphytism is a hallmark of tropical rainforests, making these environments one of the most complex ecosystems on the globe.However, to rupestrian ecosystems, existing data in the literature on this sinusiae are scarce. Thus, the floristic composition and diversity patterns and vertical distribution of vascular epiphytes were performed on the host tree focal Pseudobombax aff. campestre, sampled in granite rupestrian complexes in southern Espirito Santo state.Epiphytic species were collected between the years 2010 to 2012, and recorded 151 species, 77 genera and 21 families of vascular epiphytes, where Orchidaceae and genus pidendrum, had the highest wealth. Ten species had their first record for the Espírito Santo State and sixteen framed in a threatened category. The relationship with the most diversified phorophyte was true epiphytes characteristic, followed by holoepiphytes accidental. Analysis of similarity showed the formation of distinct floras studied areas and other surveys of the southern and southeastern Brazil. Quantitative study sampled 90 phorophytes divided into five ecological zones. In each zone scores were given to the dominance of epiphytic species according to their biomass. We recorded 142 species of vascular epiphytes with Shannon index of 4.44 and equity of 0.90. No species is widely emphasized in importance, being Rhipsalis teres, Vriesea lubbersii, Bulbophyllum cantagallense and Microgramma squamulosa those that occupied the top positions. Richness, diversity and fairness were associated with shallow roots, where holoepiphytes accidental and voluntary abound. The species distribution along the areas of phorophytes showed greater floristic similarity between the strata of proximity, which distinguished two groups, one cup and one base chorophytes. The ordering of the 35 main species revealed the existence of 13 species associated with some zone P. aff. campestre, however, 63% of species had a wide distribution of areas phorophytes. The diameter and height of phorophytes showed high correlation with wealth epiphytic. The high richness and diversity found on Pseudobombax aff. campestre, certainly relates to the morphological structures of this peculiar phorophyte, allowing ample colonization of epiphytic flora. This phorophyte certainly guarded one epiphytic flora past tense, arising from forests that made contact with the boundaries of the outcrops studied, this being a sort of nucleadora biodiversity on rocky outcrops in southeastern Brazil.